The β3 subunit of the integrin αIIbβ3 regulates αIIb-mediated outside-in signaling - Liu, Junling (© 2005 by The American Society of Hematology, 2005)
Bidirectional signaling is an essential feature of αIIbβ3 function. The αIIb cytoplasmic domain negatively regulates β3-mediated inside-out signaling, but little is known about the regulation of αIIb-mediated outside-in signaling. We show that αIIb-mediated outside-in signaling is enhanced in platelets of a patient lacking the terminal 39 residues of the β3 cytoplasmic tail. This enhanced signaling was detected as thromboxane A(2) (TxA(2)) production and granule secretion, and required ligand cross-linking of αIIbβ3 and platelet aggregation. This outside-in signaling was specifically inhibited by a palmitoylated version of a β3 peptide corresponding to cytoplasmic domain residues R724-R734. Unlike the palmitoylated peptide, the nonpalmitoylated β3 peptide could not cross the platelet membrane and did not inhibit this outside-in signaling. The physiologic relevance of this β3-mediated negative regulation of αIIb outside-in signaling was demonstrated in normal platelets treated with the palmitoylated peptide and a physiologic agonist. Binding of αIIbβ3 complexes to immobilized peptides demonstrated that a peptide corresponding to β3 residues R724-R734 appears to bind to an αIIb cytoplasmic domain peptide containing residues K989-D1002, but not to control peptides. These results demonstrate that αIIb-mediated outside-in signaling resulting in TxA(2) production and granule secretion is negatively regulated by a sequence of residues in the membrane distal β3 cytoplasmic domain sequence RKEFAKFEEER.